Texts—Textures—Intertexts: Brian Cherney’s Transfiguration (1990) - Ricketts, Matthew (Intersections)

(untitled) (Canadian University Music Society / Société de musique des universités canadiennes, 2017)
Transfiguration ([1990] 1991) is one of Brian Cherney’s most ambitious compositions. Scored for large orchestra, the piece explores how memories transfigure reality and what that process might sound like. Cherney weaves together a dizzying mise en abyme of quotations—from the canonic repertoire, simulacra of European folk tunes, and his own earlier music (including most prominently Shekhinah for solo viola from [1988] 1992). Orchestral textures alternatively obscure and reveal material both directly and indirectly related to and inspired by the Holocaust, including the photograph of a Hungarian Jewish woman at Auschwitz who haunts the work. The fleeting figure of this unknown woman is represented in the way that material is transfigured—lost, re-emerging, and lost again—throughout. This article focuses on Transfiguration as an apotheosis of Cherney’s interest in the relationship between orchestral texture and intertextuality.